Frequency Diverse Array Auto-Scanning Beam Characteristics and Potential Radar Applications - Wen-Qin Wang (IEEE Access, 2022)
Different from the phased-array with the same carrier frequency for all elements providing only angle-dependent beampattern, frequency diverse array (FDA) using a small frequency offset across its array elements offers new application capabilities due to its both angle and range dependent beampattern, which allows auto beam-scanning capability even without the employment of phase shifters, which are required in phased-array. This paper studied FDA auto-scanning beam characteristics and several potential radar applications. The FDA auto-scanning beam characteristics including range and angle coupling, beam auto-scanning rate and integral array again are analyzed. To fully utilize FDA specific auto-scanning beam characteristics, several potential applications such as radio frequency (RF) stealth or RF localization deception, range-ambiguous clutter suppression and mainlobe interference suppression are discussed. Moreover, several discussions about space-time adaptive processing and possible future investigations are provided. This paper is formulated from a top-level system description, which aims to introduce this promising FDA technique to radar community so that more investigations can be facilitated.